The Share of Wages in the National Income : Ban enquiry into the theory of distribution - Hahn, F.H. (London : Weidenfeld and Nicolson, 1972)
This book is largely concerned with an exploration of the consequences for the theory of distribution of a postulated difference in the savings propensities out of wages and profits.
Includes bibliographical references
osa;16/08/17
Loans
Keywords: Wages -Mathematical models; National income